Optimizing Workstation Design for Standing Work System in an Electronics Assembly Work - Baba Mohd DEROS; Abdul Rahman Mohd YUSOFF; Solehah Jamilah ISMAIL; Dian Darina Indah DARUIS (Tehran University of Medical Sciences, 2016)
Background: Standing workstation can be a strategic approach for many electronics manufacturers to achieve work optimization. However, the well-being of the workers has become a great issue for both workers and employers. The main objective of this research was to study the effects of standing working posture on the workers and their impact to workers' health and productivity and then to re-design and optimize their workstations to a better the working posture. Methods: The methods used in this study included ergonomics risk assessment using Standing Risk Assessment (SRA), Body Parts Symptoms Analysis (BPSA) and anthropometric data measurements. The subjects in this study were 146 female workers. This case study was carried out in 2011 in a multinational electronics company situated in Beranang Industrial Area, Selangor, Malaysia. Results: After the re-design, a 26% floor space savings, as well as 30% improvement in productivity, quality and reduction in Work In Progress (WIP) was seen. The risk level was at level 2, which was considerably low. Nevertheless, the calculated numbers of industrial accidents and total lost hours were reduced sharply by implementing correct standing cell operation. Conclusion: Standing while working might be the most productive posture in manufacturing and assembly work. However, it can be the opposite if the workers are exposed to musculoskeletal disorders and fatigue because of working standing for too long.   Keywords: Standing work, Workstation design, Ergonomic, Standing risk assessment